2017
DOI: 10.1007/s11011-016-9947-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central administration of T3 improved the histological changes, memory and the dentate gyrus electrophysiological activity in an animal model of Alzheimer’s disease

Abstract: The amyloid beta (Aβ) induced Alzheimer's disease (AD) is associated with formation the amyloid plaques, cognitive impairments and decline in spontaneous discharge of neurons. In the current study, we evaluated the effect of subcutaneous (S. C) and intrahippocampal (I. H) administrations of triiodothyronine (T3) on the histological changes, memory and the dentate gyrus (DG) electrophysiological activity in an animal model of AD. Eighty adult male Wistar rats (250-300 g) were divided randomly into five groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Moreover, another study reported that hypofunction of the adenohypophysis due to circadian rhythm disturbances in AD decreased TSH levels (34). Although it is not elusive whether thyroid dysregulation occurs before or after the onset of AD, treatment with thyroid hormone restoration has been reported to potentially improve cognitive deficits in animal studies (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another study reported that hypofunction of the adenohypophysis due to circadian rhythm disturbances in AD decreased TSH levels (34). Although it is not elusive whether thyroid dysregulation occurs before or after the onset of AD, treatment with thyroid hormone restoration has been reported to potentially improve cognitive deficits in animal studies (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study reported that hypofunction of the adenohypophysis due to circadian rhythm disturbances in AD decreased TSH levels ( 34 ). Although it is not elusive whether thyroid dysregulation occurs before or after the onset of AD, treatment with thyroid hormone restoration has been reported to potentially improve cognitive deficits in animal studies ( 35 37 ). We performed an additional analysis excluding individuals who were diagnosed with thyroid disease 2 years before the index date to compensate for the characteristics of this study, which had a case-control design ( Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this work is very relevant, the mechanisms by which the decreased serum free T3 levels increase the risk of developing this neurodegenerative disease have not been elucidated. Moreover, peripheral and central administration of T3 improved memory de cits in AD animal models (Farbood et al 2017). However, the clinical signi cance of those ndings remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, hypothyroidism reduced hippocampal neurogenesis (10) and in CA1 neurons it impaired long-term potentiation (LTP), that was then restored by TH administration (11,12). Moreover, TH have been demonstrated to influence amyloid precursor protein (APP) transcription, the alternative splicing of APP mRNA, APP protein processing (13)(14)(15) and to rescue memory deficits in AD rodent models (16)(17)(18)(19). These results suggest that TH may exert a neuroprotective role against β-amyloid (Aβ)dependent neuronal impairment, which is assumed to be one of the pathophysiological mechanisms involved in AD.…”
Section: Introductionmentioning
confidence: 99%